Humanitarian Crisis and the Arduous Path to Principled Pluralism: A Politico-Theological Analysis on Indian and Turkish Foreign Policies (2014-2019) - Hadza min Fadhli Robby (Journal of Islamic World and Politics, 2021)
This research aims to analyze the influence of political theology in the foreign policy of Indian and Turkish from 2014 to 2019. India and Turkey used political theology as one of the essential considerations for the conduct of foreign policies during the humanitarian crisis. Both countries were trying to conduct “politics of salvation” to protect their fellow faithful from the oppression in the neighboring regions. While conducting its politics of salvation in their foreign policies, India and Turkey were trying to protect their fellow faithful from the oppression from the constructed others. This research argues that the politics of salvation in its foreign policy will influence both countries’ religious freedom and secularism. This research would like to utilize the concept of “politics of principled pluralism” that Robert Joustra developed. In its analysis, this research engages with several articles from news outlets and research journals to construct arguments on the conduct of the foreign policy of India and Turkey in times of humanitarian crisis. This research found that India and Turkey had tried to implement their version of “politics of salvation” that deteriorate religious freedom and inclusive democracy.